The interaction of α-amylase with mycoprotein: Diffusion through the fungal cell wall, enzyme entrapment, and potential physiological implications. (November 2020) - Colosimo, Raffaele; Warren, Frederick J.; Edwards, Cathrina H.; Finnigan, Tim J.A.; Wilde, Pete J.
Abstract: This study investigated the in vitro interaction of α-amylase with mycoprotein and the subsequent impact on carbohydrate digestion. Mycoprotein is a food ingredient obtained from the fermentation of the filamentous fungus Fusarium venenatum, whose hyphal structure is determined by cell walls mainly composed of β-glucans and chitin. Simulated digestion showed that α-amylase hydrolysed the intracellular glycogen from within the mycoprotein hyphae, as shown by the increase in concentration of reducing sugars (glycogen amylolysis products) in the digestion fluid over time. The presence of fungal cell walls slowed down the kinetics of reducing sugar release during digestion when compared to extracted glycogen (no cell walls). The enzyme was able to diffuse through the fungal cell walls as evident from confocal-laser-scanning-microscopy which showed the presence of FITC-labelled α-amylase inside the cells, and the reduction of the free enzyme concentration in the surrounding solution. Consequently, in vitro digestion of starch in the presence of increasing concentrations of mycoprotein showed a reduced starch hydrolysis rate by α-amylase. Starch hydrolysis after 12 min of in vitro digestion was decreased from a value of 18.19 wt% without mycoprotein to 4.47 wt% (***p-value < 0.001) in the presence of the highest mycoprotein concentration. Kinetic analyses of starch digestion by amylase in the presence of different concentrations of mycoprotein revealed a linear reversible mixed inhibition. These findings are relevant to understanding the mechanisms by which mycoprotein has been observed to attenuate postprandial glycaemia/insulinemia and may have potential applications in food industry processes that aim to reduce/limit starch hydrolysis. Graphical abstract: Image 1 Highlights: The porosity of mycoprotein fungal cell wall permitted the diffusion of α-amylase into the cells. The diffusion of α-amylase through the cell wall results in the entrapment of the enzyme within the hyphal matrix. The entrapment of the enzyme reduced overall enzymatic activity and consequently reduced starch hydrolysis. The protein fraction within the cells may also play a role in reducing starch hydrolysis. The reduced starch hydrolysis may explain the reduced insulin response observed after mycoprotein consumption in vivo.